Cohesion grupal in the Aquatic Pole. A necessary theoretical reflection (Revista científica Olimpia, 2015)
In the physical activity and the sport the social dexterities are considered elements dinamizadores that condition the good operation of a sport team. Of for yes, when becoming the sport a human activity with extraordinary potentialities for the formation of values, abilities, habits, capacities, among other, therefore a preparation process should be profiled in the more and more scientific sportsmen on the part of the technicians and trainers, and specialists of the psychology of the sport. The cohesion grope is a factor fundamental sociopsicológico in the sport of Aquatic Pole, where the activities and tasks are carried out of interrelated form and intercondicionadas among their members, it requires for ends, of a favorable treatment of all those factors that guarantee the achievement of the objectives and goals traced by the teams. In this type of alone sport it is possible the sport success if the members act, they feel and they think in a combined way, based on previously established objectives and common necessities. The present article has like base the master studies in psychology deport of the author and the fervent necessity of investigations and interventions in sport teams in the county of Granma, specifically in the sport of Aquatic Pole in the school categories. This work pursues as objective a bibliographical revision about the cohesion grope in the team sports. He/she was carried out a search from investigations of the social psychology as beginner of these studies and the works carried out from the psychology of the sport regarding the topic. They were object of revision digital magazines, electronic data and pertinent written documents to the topic in question. He/she offers in the work positions and the main authors' theoretical boardings on the cohesion grope.
Keywords: cohesion gropes; sport teams; aquatic pole; bibliographical revision